Sustaining Cell Therapy Quality through Shared Responsibility: A Call for Equitable FACT Inspectorate Participation - Suzanne Birnley; Michele W Sugrue; Angelica Vivero; R. Alejandro Sica; Elias Kalouche; Daniel Kota; Donna Salzman; Renee Smilee; Ibrahim Ahmed; Arunkumar Modi; Guy Klamer; Phillip Johnson; et al. (Blood Advances, 2026)
This paper highlights a critical challenge in the FACT peer-accreditation system: a growing imbalance between the rising number of accredited and applicant organizations and the limited pool of volunteer inspectors. This imbalance places a disproportionate burden on current inspectors, concentrates accreditation expertise within a small subset of programs, and threatens the efficiency of the peer-review model. The paper presents compelling evidence that organizations contributing to the inspectorate gain measurable benefits. These include stronger audit performance in renewal cycles, access to education in quality standards and best practices, and broader professional networks. The paper concludes with a call to action: accredited organizations should share responsibility and contribute equitably to the FACT inspectorate to maintain the quality and sustainability of the accreditation process.